Upaya Meningkatkan Hasil Belajar Siswa Melalui Layanan Penguasaan Konten Bidang Bimbingan Belajar Pada Siswa Kelas X SMA Negeri 1 Bintang Bayu - Yusna Hasibuan (Journal of Creative Student Research, 2024)
The aim of this research is to improve the learning outcomes of class X SMA Negeri Bintang Bayu students through the implementation of content mastery services in the field of tutoring. The population in this study were all class Samples were taken using a purpose sampling technique, namely taking samples according to the research objectives. In determining the sample, we used classes whose student learning outcomes in science subjects were relatively low compared to other classes. The number of samples taken was 30 people. This research uses a type of action research. This research uses two cycles. The data analysis technique used is to find the percentage using the formula, P= f/n x 100%. The research results show that content mastery services in the field of tutoring can be applied in an effort to improve the learning outcomes of class X students at SMA Negeri Bintang Bayu. This is known based on the comparison of student learning outcomes which increased after receiving content mastery services. In cycle I, students whose learning outcomes increased by 41.65% (fair), while in cycle II students whose learning outcomes increased by 73.35% (good), which means the action hypothesis was accepted.